Supply chain single vendor: Single buyer inventory model with price-dependent demand - Mona Ahmadi Rad; Farid Khoshalhan; Mostafa Setak (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: The aim of this article is developing an integrated production-inventory-marketing model for a two-stage supply chain. The demand rate is considered as the Iso-elastic decreasing function of the selling price. The main research goal of the article is to obtain the optimal values of the selling price, order quantity and number of shipments for the proposed model under independent and also joint optimization. In addition, the effects of the model's parameters on the optimal solution are investigated. Design/methodology/approach: Mathematical modeling is used to obtain the joint total profit function of the supply chain. Then, the iterative solution algorithm is presented to solve the model and determine the optimal solution. Findings and Originality/value: It is observed that under joint optimization, the demand rate and the supply chain's profit are higher than their values under independent optimization, especially for the more price sensitive demand. Therefore, coordination between the buyer and the vendor is advantageous for the supply chain. On the other hand, joint optimization will be less beneficial when there isn't a significant difference between the buyer's and the vendor's holding costs. Originality/value: The contribution of the article is determining the ordering and pricing policy jointly in the supply chain, which contains one vendor and one buyer while the demand rate is the Iso-elastic function of the selling price.
Keywords: 650; integrated inventory; pricing; vendor; buyer